2021
DOI: 10.1055/a-1487-6415
|View full text |Cite
|
Sign up to set email alerts
|

Lebensqualität nach geschlechtsangleichenden Operationen – eine Übersicht

Abstract: Zusammenfassung Hintergrund Bei Personen mit Geschlechtsinkongruenz wird eine Verminderung der Lebensqualität durch zahlreiche Studien belegt. Die hohe psychische Belastung führt zu depressiven Erkrankungen, Angststörungen und gegenüber der Normbevölkerung erhöhter Suizidalität. Auch soziale Limitationen führen zu verminderter Lebensqualität. Die Möglichkeit geschlechtsangleichender Operationen wird zunehmend wahrgenommen, stellt jedoch einen radikalen Eingriff in das Leben dieser Patienten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We included 2317 TGNB patients who underwent CMS in the cohort. The median (IQR) age was 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years, and the median (IQR) BMI was 27.37 (23.44-32.2) kg/m 2 . Figure 1 illustrates the distribution of BMI within our study population.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We included 2317 TGNB patients who underwent CMS in the cohort. The median (IQR) age was 25 (21)(22)(23)(24)(25)(26)(27)(28)(29)(30) years, and the median (IQR) BMI was 27.37 (23.44-32.2) kg/m 2 . Figure 1 illustrates the distribution of BMI within our study population.…”
Section: Resultsmentioning
confidence: 99%
“…Nonobese patients (BMI <30 kg/m 2 ) were significantly younger than patients with BMI categories 1 through 3 (30-44.9 kg/m 2 ) [median (IQR) age, 24 (21-29) vs 26 through 28 (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) years; P < 0.001]. Nonobese patients had significantly shorter operating times compared with patients with BMI category 3 (40-44.9 kg/m 2 ) [median (IQR) operating time, 141 (110-183.5) vs 154 (120-198) minutes; P = 0.006].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAS combined with cross-sex hormones and psychological therapy can improve the quality of life of transgender patients [ 27 ]. An enhancement in quality of life following GAS is well established [ 28 ]. In numerous studies, individuals undergoing GAS have reported notable enhancements in body image and an increased level of satisfaction with their overall lifestyle [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%